Case Report: A Chinese family with MYH9-RD caused by MYH9 p.E1841K mutation exhibiting widespread may-hegglin inclusions - Lian, Xiaoqiang; Li, Haixia; Hao, Jihong; Li, Haixin; Xu, Ling; Zhang, Shuxia; Cao, Li; Li, Ruimin (Frontiers in Pediatrics, 2025)
IntroductionMYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia, with a risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. Due to its presentation of isolated thrombocytopenia, it is frequently misdiagnosed as immune thrombocytopenic purpura (ITP).MethodsA 10-year-old girl with an initial diagnosis of ITP was evaluated, based on isolated thrombocytopenia and intermittent epistaxis. Clinical assessments included peripheral blood and bone marrow smear examinations to observe cellular morphology. Family history was collected to identify potential hereditary associations. Genetic testing was performed to detect potential pathogenic mutations.ResultsPeripheral blood and bone marrow smears revealed giant platelets, along with blue inclusions in neutrophils, eosinophils, and monocytes—key cytological features of MYH9-RD. Family history investigation showed thrombocytopenia in the patient's mother and maternal grandmother; additionally, the mother had mild hearing impairment, and the maternal grandmother had died of renal failure. Genetic testing confirmed the presence of the MYH9 p.E1841K mutation in the patient, which was inherited from her mother. Based on these findings, the diagnosis was revised from ITP to MYH9-RD.DiscussionThis case emphasizes that MYH9-RD should be considered in the differential diagnosis of unexplained thrombocytopenia, particularly when accompanied by characteristic cytological findings (e.g., giant platelets, blue inclusions in leukocytes) and a positive family history of related manifestations. The consistency of phenotypes within the affected family supports the importance of genetic screening and long-term follow-up for relatives of confirmed cases to enable early detection and management of potential complications.